Human rights and education: The case of the Negev Bedouins - Tarrow, Norma (Hagar: Studies in Society and Culture, 2008)
This paper builds upon research conducted in 1977, presented at the WCCES World Congress in London (published in Bernstein-Tarrow, 1978), as well as subsequent research and publications in the field of human rights and human rights education. Based on the assumption (reinforced by numerous international agreements) that education is a human right and that education about human rights is their ultimate sanction, the paper analyzes the situation of the Bedouins of the Negev 30 years later, examining the relationship between demographic factors, socioeconomic factors and political issues, on the one hand, and human rights in general and the right to education in particular, on the other. In terms of Israel’s responsibilities as signatory to various international agreements, assuring equal rights to its citizens, consideration is given to such issues as educational objectives, budget, staffing, dropouts and the role of non-governmental organizations dedicated to ensuring the right to education and education about human rights.